Influence of stent design and use of protection devices on outcome of carotid artery stenting: a pooled analysis of individual patient data - Wodarg, Fritz; Ringleb, Peter A. (Journal of neuroInterventional surgery, 2018)
Background and purpose: Carotid artery stenting is an alternative to endarterectomy for the treatment of symptomatic carotid stenosis but was associated with a higher risk of procedural stroke or death in randomized controlled trials (RCTs). Technical aspects of treatment may partly explain these results. The purpose of this analysis was to investigate the influence of technical aspects such as stent design or the use of protection devices, as well as clinical variables, on procedural risk. Methods: We pooled data of 1557 individual patients receiving stent treatment in three large RCTs comparing stenting versus endarterectomy for symptomatic carotid stenosis. The primary outcome event was any procedural stroke or death occurring within 30 days after stenting. Results: Procedural stroke or death occurred significantly more often with the use of open-cell stents (61/595 patients, 10.3%) than with closed-cell stents (58/962 patients, 6.0%; RR 1.76; 95% CI 1.23 to 2.52; P=0.002). Procedural stroke or death occurred in 76/950 patients (8.0%) treated with protection devices (predominantly distal filters) and in 43/607 (7.1%) treated without protection devices (RR 1.10; 95% CI 0.71 to 1.70; P=0.67). Clinical variables predicting the primary outcome event were age, severity of the qualifying event, history of prior stroke, and level of disability at baseline. The effect of stent design remained similar after adjustment for these variables. Conclusions: In symptomatic carotid stenosis, the use of stents with a closed-cell design is independently associated with a lower risk of procedural stroke or death compared with open-cell stents. Filter-type protection devices do not appear to reduce procedural risk.